Method for preparing copper nanowires and copper nanowires prepared therefrom

By mixing the copper precursor solution with the reducing agent solution, the hydrothermal reaction is carried out, and the length-to-diameter ratio of the prepared copper nanowires reaches 600 to 800, and the morphology is uniform, which solves the problem of unsatisfactory length-to-diameter ratio of the copper nanowires and uneven shapes in the prior art, and the preparation method is simple and the conditions are mild.

CN114603154BActive Publication Date: 2025-03-21WUHAN TEXTILE UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210281254.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-22
Publication Date
2025-03-21
Estimated Expiration
2042-03-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prepare copper nanowires, resulting in unsatisfactory aspect ratios and uneven shapes.

Method used

Copper nanowires were prepared by mixing the copper precursor solution with a reducing agent solution, a cosolvent, an organic capping agent and a co-capsule ligand in sequence, and then undergoing a hydrothermal reaction. The method includes reacting for 3 to 5 h at a temperature of 100°C to 160°C, followed by precipitation and separation to obtain copper nanowires.

Benefits of technology

The copper nanowires with an aspect ratio of 600 to 800 were achieved, and the copper nanowires with a length of 60μm to 120μm accounted for more than 80%, and the morphology was uniform. At the same time, the preparation method was simple, the reaction conditions were mild, and the repeatability was good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114603154B_ABST
    Figure CN114603154B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing copper nanowires, comprising the following steps: providing a copper precursor solution, a reducing agent solution, a cosolvent, an organic capping agent, and a co-capping ligand; mixing the copper precursor solution with the reducing agent solution to obtain a first mixed solution; mixing the cosolvent with the first mixed solution to obtain a second mixed solution; mixing the organic capping agent with the second mixed solution to obtain a third mixed solution; mixing the co-capping ligand with the third mixed solution to obtain a fourth mixed solution; reacting the fourth mixed solution at a temperature of 100°C to 160°C for 3h to 5h to obtain a solid-liquid mixture; separating the solid-liquid mixture after precipitation to obtain an upper layer of liquid, centrifuging the upper layer of liquid to obtain a solid substance, and preparing copper nanowires. The prepared copper nanowires have an ideal aspect ratio, uniform morphology, and are characterized by simple method, mild reaction conditions, and good repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation, and in particular to a method for preparing a copper nanowire and the prepared copper nanowire. Background Art

[0002] Transparent conductors have become an important component in the manufacture of next-generation flexible optical devices and are widely used as basic components in various technologies, such as solar cells, flat-panel displays, organic light-emitting devices, electrochromic windows, etc. The most commonly used transparent conductor materials are metal oxides, such as indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide. The synthesis of these transparent conductive oxides (TCOs) is very complex and costly.

[0003] In the past decade, as alternatives to TCO, materials such as carbon nanotubes, graphene, conductive polymers, and metal nanomaterials have been widely studied. Among them, metal nanomaterials have attracted particular attention due to their excellent optoelectronic properties. Compared with other metal nanomaterials, copper nanowires have significant characteristics such as affordability, high conductivity, and low sheet resistance. Copper nanowires with high aspect ratios can effectively reduce sheet resistance and provide more areas for light to pass through. However, the aspect ratio of copper nanowires prepared by general methods is not ideal and the morphology is not uniform. Summary of the invention

[0004] Based on this, it is necessary to provide a method for preparing copper nanowires and the copper nanowires prepared therefrom to address the technical problems of unsatisfactory aspect ratio and uneven morphology of copper nanowires.

[0005] The present application provides a method for preparing copper nanowires according to an embodiment, wherein the method for preparing copper nanowires comprises the following steps:

[0006] Provide copper precursor solution, reducing agent solution, co-solvent, organic capping agent, and co-capping ligand;

[0007] Mixing the copper precursor solution with the reducing agent solution to obtain a first mixed solution;

[0008] mixing the co-solvent with the first mixed solution to obtain a second mixed solution;

[0009] Mixing the organic capping agent with the second mixed solution to obtain a third mixed solution;

[0010] Mixing the co-capping ligand with the third mixed solution to obtain a fourth mixed solution;

[0011] Placing the fourth mixed solution in a hydrothermal reaction kettle, reacting at a temperature of 100° C. to 160° C. for 3 h to 5 h to obtain a solid-liquid mixture;

[0012] The solid-liquid mixture is precipitated and separated to obtain an upper liquid, and the upper liquid is centrifuged to obtain a solid substance to prepare copper nanowires.

[0013] In one embodiment, in the method for preparing the copper nanowires:

[0014] The copper precursor solution and the reducing agent solution are mixed by dropping the reducing agent solution into the copper precursor solution;

[0015] The co-solvent is mixed with the first mixed solution by dropping the co-solvent into the first mixed solution;

[0016] The organic capping agent and the second mixed solution are mixed by dropping the organic capping agent into the second mixed solution;

[0017] The co-capping ligand and the third mixed solution are mixed in a manner of dropping the co-capping ligand into the third mixed solution.

[0018] In one embodiment, the copper precursor solution is an aqueous solution of a divalent copper salt, and the molar concentration of the copper precursor solution is 44.6 mmol / L to 78.7 mmol / L.

[0019] In one embodiment, the mass concentration of the reducing agent solution is a molar concentration of 55.5 mmol / L to 122.1 mmol / L.

[0020] In one embodiment, the co-solvent is any one or more of glycerol, ethylene glycol water, hexadecylamine, oleylamine, and oleic acid.

[0021] In one embodiment, the organic capping agent is any one or more of oleylamine, ethylenediamine, hexadecylamine, and hexadecyltrimethylammonium chloride.

[0022] In one embodiment, the co-capping ligand is any one or more of oleic acid, ammonium chloride, and potassium bromide.

[0023] In one embodiment, in the step of preparing the first mixed solution, the volume ratio of the copper precursor solution to the reducing agent solution is 1:1;

[0024] In the step of preparing the second mixed solution, the volume ratio of the co-solvent to the first mixed solution is 1:4;

[0025] In the step of preparing the third mixed solution, the volume ratio of the organic capping agent to the second mixed solution is 1:6.25;

[0026] In the step of preparing the fourth mixed solution, the volume ratio of the co-capping ligand to the third mixed solution is 1:(725-1208).

[0027] In one embodiment, the organic capping agent is oleylamine, the co-capping ligand is oleic acid, and the mass ratio of the organic capping agent to the co-capping embryo is (77-166):1.

[0028] The present application also provides a copper nanowire of an embodiment, which is prepared by the above-mentioned preparation method; the aspect ratio of the copper nanowire is 600-800, and the copper nanowire with a length of 60μm-120μm accounts for more than 80%.

[0029] The above-mentioned method for preparing copper nanowires adopts a method in which a copper precursor solution is mixed with a reducing agent solution, a co-solvent, an organic capping agent and a co-capping ligand in sequence and then heated to react. The aspect ratio of the prepared copper nanowires reaches 600-800, and the aspect ratio is ideal; copper nanowires with a length of 60μm to 120μm account for more than 80%, and the morphology is uniform; in addition, the preparation method also has the characteristics of simple method, mild reaction conditions and good repeatability.

[0030] Furthermore, the mass ratio of the copper precursor to the reducing agent also has an important influence on the uniformity and yield of the prepared copper nanowires. The length and yield of the prepared copper nanowires have different change trends when the mass ratio of the copper precursor to the reducing agent is different.

[0031] Furthermore, the present application adopts oleylamine as an organic capping agent, and oleic acid as a co-capping ligand in combination with oleylamine, so that the mass ratio of the organic capping agent to the co-capping embryo is (77-166):1, thereby being able to control the growth of the diameter and length of the copper nanowires, so that the diameter of the prepared copper nanowires is 116nm-170nm, and the length is 60μm-120μm, thereby ensuring that the aspect ratio of the prepared copper nanowires reaches an ideal state of 600-800. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 This is a SEM image of the copper nanowires prepared in Example 3 of the present invention;

[0034] Figure 2 This is a SEM image of the copper nanowires prepared in Example 4 of the present invention;

[0035] Figure 3 This is the XRD diagram of the copper nanowires prepared in Examples 3 and 4 of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] In addition, the present application may repeat reference numbers and / or reference letters in different examples, and such repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the present application provides various specific examples of processes and materials, but those of ordinary skill in the art may recognize the application of other processes and / or the use of other materials.

[0038] The present application is described below with reference to the accompanying drawings and specific embodiments:

[0039] The preparation method of an embodiment of the present application, the preparation method of the copper nanowire comprises the following steps:

[0040] Provide copper precursor solution, reducing sugar reducing agent solution, co-solvent, organic capping agent, and co-capping ligand;

[0041] stirring and mixing the copper precursor solution and the reducing sugar reducing agent solution to obtain a first mixed solution;

[0042] Stirring and mixing the co-solvent with the first mixed solution to obtain a second mixed solution;

[0043] Stirring and mixing the organic capping agent and the second mixed solution to obtain a third mixed solution;

[0044] stirring and mixing the co-capping ligand and the third mixed solution to obtain a fourth mixed solution;

[0045] The fourth mixed solution is placed in a hydrothermal reaction kettle, and reacted at a temperature of 100° C. to 160° C. for 3 h to 5 h to obtain a solid-liquid mixture;

[0046] The solid-liquid mixture is precipitated and separated to obtain the upper liquid, and the upper liquid is centrifuged to obtain the solid matter to obtain the copper nanowires.

[0047] In this embodiment, a method is adopted in which a copper precursor solution is mixed with a reducing agent solution, a co-solvent, an organic capping agent and a co-capping ligand and then heated to react, and the aspect ratio of the prepared copper nanowires reaches 600-800, which is an ideal aspect ratio; copper nanowires with a length of 60μm to 120μm account for more than 80%, and have a uniform morphology; in addition, the preparation method is also characterized by a simple method, mild reaction conditions and good repeatability.

[0048] In the above embodiments, the reactants can be mixed evenly by stirring or the like.

[0049] As an optional implementation, in the method for preparing copper nanowires of this embodiment:

[0050] The copper precursor solution and the reducing agent solution are mixed by dropping the reducing agent solution into the copper precursor solution;

[0051] The co-solvent and the first mixed solution are mixed by dropping the co-solvent into the first mixed solution;

[0052] The organic capping agent and the second mixed solution are mixed by dropping the organic capping agent into the second mixed solution;

[0053] The co-capping ligand and the third mixed solution are mixed in a manner of dropping the co-capping ligand into the third mixed solution.

[0054] In this embodiment, the reactants are mixed by dropping, and preferably, the reactants can be further mixed evenly by stirring so that the reactants can react better.

[0055] As an optional embodiment, in this embodiment, the copper precursor solution is an aqueous solution of a divalent copper salt, and the molar concentration of the copper precursor solution is 44.6 mmol / L to 78.7 mmol / L. Further optionally, the divalent copper is selected from any one or more of copper chloride, copper nitrate, copper sulfate, copper acetate, copper bromide, copper iodide, copper phosphate, copper carbonate, and copper acetylacetonate.

[0056] As an optional embodiment, the mass concentration of the reducing agent solution in this embodiment is a molar concentration of 55.5mmol / L to 122.1mmol / L. Further optionally, the reducing agent is selected from glucose, ascorbic acid, oxalic acid, formic acid, hydrazine hydrate, ethylene glycol, benzoin, hexadecylamine and other reagents with reducing effects. Further preferably, the reducing agent is preferably glucose.

[0057] As an optional implementation manner, the co-solvent in this embodiment is selected from any one or more of glycerol, ethylene glycol, water, hexadecylamine, oleylamine, and oleic acid.

[0058] As an optional implementation, the organic end-capping agent in this embodiment is selected from any one or more of oleylamine, ethylenediamine, hexadecylamine, and hexadecyltrimethylammonium chloride.

[0059] As an optional implementation manner, the co-capping ligand in this embodiment is selected from any one or more of oleic acid, ammonium chloride, and potassium bromide.

[0060] As an optional implementation, in the method for preparing nanowires of this embodiment, in the step of preparing the first mixed solution, the volume ratio of the copper precursor solution to the reducing agent solution is 1:1;

[0061] In the step of preparing the second mixed solution, the volume ratio of the co-solvent to the first mixed solution is 1:4;

[0062] In the step of preparing the third mixed solution, the volume ratio of the organic capping agent to the second mixed solution is 1:6.25;

[0063] In the step of preparing the fourth mixed solution, the volume ratio of the co-capping ligand to the third mixed solution is 1:(725-1208).

[0064] As a further preferred embodiment, in this embodiment, the organic capping agent is oleylamine, the co-capping ligand is oleic acid, and the mass ratio of the organic capping agent to the co-capping embryo is (77-166):1.

[0065] The present application also proposes a copper nanowire according to an embodiment, which is prepared by the above-mentioned preparation method; the aspect ratio of the copper nanowire is 600-800, and the copper nanowire with a length of 60μm-120μm accounts for more than 80%.

[0066] First, it should be noted that the reaction reagents used in the following examples are all commercially available reagents of analytical purity.

[0067] Example 1

[0068] A copper chloride deionized water solution with a mass concentration of 6 g / L and a glucose deionized water solution with a mass concentration of 12 g / L were prepared respectively. 50 mL of glucose deionized water solution was added dropwise to 50 mL of copper chloride deionized water solution to obtain a first mixed solution, and then 25 mL of glycerol analytical pure reagent was added dropwise to the first mixed solution to obtain a second mixed solution, and then 20 mL of oleylamine analytical pure reagent was added dropwise to the second mixed solution to obtain a third mixed solution, and then 200 μL of oleic acid analytical pure reagent was added dropwise to the third mixed solution to obtain a fourth mixed solution. Finally, the fourth mixed solution was placed in a reactor at 120 ° C for 4 hours. The solid-liquid mixture obtained after the reaction was precipitated and then solid-liquid separation was performed. The upper liquid was placed in a centrifuge and centrifuged at 4000 rpm for 5 minutes. The centrifugal precipitate was the copper nanowire. The obtained copper nanowire was washed 2 to 3 times with n-hexane and stored in n-hexane.

[0069] After testing, the yield of the copper nanowires was 70.3%, the average length of the copper nanowires was 80 μm, the copper nanowires with a length of 70 μm to 90 μm accounted for 86% of the product, the average diameter was 133 nm, and the aspect ratio was 602.

[0070] Example 2

[0071] Prepare a deionized copper chloride solution with a mass concentration of 6g / L and a deionized glucose solution with a mass concentration of 12g / L respectively. First, add 50mL of deionized glucose solution to 50mL of deionized copper chloride solution to obtain a first mixed solution, then add 25mL of analytically pure glycerol reagent to the first mixed solution to obtain a second mixed solution, then add 20mL of analytically pure oleylamine reagent to the second mixed solution to obtain a third mixed solution, and then add 120μL of analytically pure oleic acid reagent to the third mixed solution to obtain a fourth mixed solution. Finally, the fourth mixed solution was placed at 120℃ for 4h. The solid-liquid mixture obtained after the reaction was precipitated and then solid-liquid separation was performed. The upper liquid was placed in a centrifuge and centrifuged at 4000rpm for 5min. The centrifuged precipitate was the copper nanowire. The obtained copper nanowire was washed 2 to 3 times with n-hexane and stored in n-hexane.

[0072] After testing, the yield of the copper nanowires was 73.4%, the average length of the copper nanowires was 70 μm, the copper nanowires with a length of 65 μm to 75 μm accounted for 83% of the product, the average diameter was 126 nm, and the aspect ratio was 556.

[0073] Example 3

[0074] Prepare a copper chloride deionized water solution with a mass concentration of 8g / L and a glucose deionized water solution with a mass concentration of 12g / L respectively. First, add 50mL of glucose deionized water solution to 50mL of copper chloride deionized water solution to obtain a first mixed solution, then add 25mL of glycerol analytical pure reagent to the first mixed solution to obtain a second mixed solution, then add 20mL of oleylamine analytical pure reagent to the second mixed solution to obtain a third mixed solution, and then add 200μL of oleic acid analytical pure reagent to the third mixed solution to obtain a fourth mixed solution. Finally, the fourth mixed solution was placed at 120℃ for 4h. The solid-liquid mixture obtained after the reaction was precipitated and then solid-liquid separation was performed. The upper liquid was placed in a centrifuge and centrifuged at 4000rpm for 5min. The centrifugal precipitate was the copper nanowire. The obtained copper nanowire was washed 2 to 3 times with n-hexane and stored in n-hexane.

[0075] The yield of the copper nanowires was 66.8%. Figure 1 As shown, it is an SEM image of the copper nanowires prepared in Example 3. It can be seen from the figure that the morphology of the prepared copper nanowires is uniform, the average length of the copper nanowires is 90μm, and after testing, the copper nanowires with a length of 60μm to 120μm in the product account for 88%, the average diameter is 127nm, and the aspect ratio is 708.

[0076] Example 4

[0077] Prepare a deionized copper chloride solution with a mass concentration of 9 g / L and a deionized glucose solution with a mass concentration of 12 g / L respectively. First, add 50 mL of deionized glucose solution to 50 mL of deionized copper chloride solution to obtain a first mixed solution, then add 25 mL of analytically pure glycerol reagent to the first mixed solution to obtain a second mixed solution, then add 20 mL of analytically pure oleylamine reagent to the second mixed solution to obtain a third mixed solution, and then add 200 μL of analytically pure oleic acid reagent to the third mixed solution to obtain a fourth mixed solution. Finally, the fourth mixed solution was placed at 120 ° C for 4 hours. The solid-liquid mixture obtained after the reaction was precipitated and then solid-liquid separation was performed. The upper liquid was placed in a centrifuge and centrifuged at 4000 rpm for 5 minutes. The centrifuged precipitate was the copper nanowire. The obtained copper nanowire was washed 2 to 3 times with n-hexane and stored in n-hexane.

[0078] After testing, the yield of the copper nanowires was 76.1%. Please refer to Figure 2As shown, it is a SEM image of the copper nanowires prepared in Example 4. After testing, the average length of the copper nanowires is 50 μm, the copper nanowires with a length of 40 μm to 60 μm account for 85% of the product, the average diameter is 103 nm, and the aspect ratio is 485.

[0079] Please continue reading Figure 3 , which are XRD patterns of the copper nanowires prepared in Examples 3 and 4 of the present invention. It can be seen from the figure that the characteristic crystal planes of the prepared copper nanowires are complete.

[0080] It can be seen from the experimental results of Example 1 and Example 2 that when other preparation raw materials and amounts are the same, the ratio of the organic capping agent to the co-capping ligand is different, and the aspect ratio of the prepared copper nanowire is also significantly different. When the ratio of the organic capping agent to the co-capping ligand is close to 100:1, the aspect ratio of the prepared copper nanowire is better.

[0081] It can be seen from the experimental results of Example 1 and Examples 3 and 4 that when other raw materials and amounts are the same, when the ratio of organic capping agent to co-capping ligand is close to 100:1, the lengths of the prepared copper nanowires are significantly different when the ratio of copper chloride to glucose is different. When the ratio of copper chloride to glucose is close to 2:3, the aspect ratio of the prepared copper nanowires is optimal.

[0082] Compared with the traditional use of surfactants such as dodecylamine, hexadecylamine, and octadecylamine as organic capping agents, the present application uses oleylamine as the organic capping agent, which not only makes the prepared copper nanowires longer and more uniform, but also makes the preparation method simpler, more efficient, and more productive.

[0083] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing copper nanowires, characterized in that: The method for preparing the copper nanowires comprises the following steps: Provide copper precursor solution, reducing agent solution, co-solvent, organic capping agent, and co-capping ligand; Mixing the copper precursor solution with the reducing agent solution, wherein the volume ratio of the copper precursor solution to the reducing agent solution is 1:1, to obtain a first mixed solution; Mixing the co-solvent with the first mixed solution, wherein the volume ratio of the co-solvent to the first mixed solution is 1:4, to obtain a second mixed solution; Mixing the organic capping agent with the second mixed solution, wherein the volume ratio of the organic capping agent to the second mixed solution is 1:6.25, to obtain a third mixed solution; Mixing the co-capping ligand with the third mixed solution, wherein the volume ratio of the co-capping ligand to the third mixed solution is 1:(725-1208), to obtain a fourth mixed solution; Placing the fourth mixed solution in a hydrothermal reactor, reacting at a temperature of 100° C. to 160° C. for 3 h to 5 h to obtain a solid-liquid mixture; Separating the solid-liquid mixture after precipitation to obtain an upper layer of liquid, and centrifuging the upper layer of liquid to obtain solid matter to obtain copper nanowires; Wherein, the mass ratio of the organic capping agent to the co-capping ligand is 100:1; the mass ratio of the copper chloride in the copper precursor solution to the glucose in the reducing agent solution is 2:3; The yield of the copper nanowire preparation method is more than 66%, the diameter of the copper nanowire is 116nm-170nm, the aspect ratio of the copper nanowire is 600-800, and the copper nanowire with a length of 60μm-120μm accounts for more than 80%; The cosolvent is any one or more of glycerol, ethylene glycol, water, hexadecylamine, oleylamine, and oleic acid; The organic end-capping agent is any one or more of ethylenediamine, hexadecylamine, and hexadecyltrimethylammonium chloride; The co-capping ligand is any one or more of ammonium chloride and potassium bromide.

2. The method for preparing copper nanowires according to claim 1, characterized in that: In the method for preparing the copper nanowires: The copper precursor solution and the reducing agent solution are mixed by dropping the reducing agent solution into the copper precursor solution; The co-solvent is mixed with the first mixed solution by dropping the co-solvent into the first mixed solution; The organic capping agent and the second mixed solution are mixed by dropping the organic capping agent into the second mixed solution; The co-capping ligand and the third mixed solution are mixed in a manner of dropping the co-capping ligand into the third mixed solution.

3. The method for preparing copper nanowires according to claim 1, characterized in that: The copper precursor solution is an aqueous solution of a divalent copper salt, and the molar concentration of the copper precursor solution is 44.6 mmol / L to 78.7 mmol / L.

4. The method for preparing copper nanowires according to claim 1, characterized in that: The mass concentration of the reducing agent solution is a molar concentration of 55.5 mmol / L to 122.1 mmol / L.

5. A copper nanowire, characterized in that: The copper nanowires are prepared by the preparation method according to any one of claims 1 to 4; the diameter of the copper nanowires is 116nm~170nm, the aspect ratio of the copper nanowires is 600~800, and the copper nanowires with a length of 60μm~120μm account for more than 80%.

Citation Information

Patent Citations

  • Synthesis method for copper nanowire with different length-diameter ratios

    CN104959622A